Comparative evaluation of three laparoscopic cholecystectomy techniques in rabbit’s model - Wittmaack, Monica Carolina Nery [UNESP]; Conceição, Maria Eduarda Bastos Andrade Moutinho [UNESP]; Vera, María Camila Maldonado [UNESP]; Faccini, Rachel Inamassu [UNESP]; Sembenelli, Guilherme [UNESP]; Montanhim, Gabriel Luiz [UNESP]; de Menezes, Mareliza Possa [UNESP]; Rocha, Fabiana Del Lama [UNESP]; Aires, Luiz Paulo Nogueira [UNESP]; Moraes, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2023)
Purpose: The aim of this randomized study was to compare the complications and perioperative outcome of three different techniques of laparoscopic cholecystectomy (LC). Changes in the liver function test after LC techniques were investigated. Also, we compared the degree of postoperative adhesions and histopathological changes of the liver bed. Methods: Thirty rabbits were divided into three groups: group A) Fundus-first technique by Hook dissecting instrument and Roeder Slipknot applied for cystic duct (CD) ligation; group B) conventional technique by Maryland dissecting forceps and electrothermal bipolar vessel sealing (EBVS) for CD seal; group C) conventional technique by EBVS for gallbladder (GB) dissection and CD seal. Results: Group A presented a longer GB dissection time than groups B and C. GB perforation and bleeding from tissues adjacent to GB were similar among tested groups. Gamma-glutamyl transferase and alkaline phosphatase levels increased (p ≤ 0.05) on day 3 postoperatively in group A. By the 15th postoperative day, the enzymes returned to the preoperative values. Transient elevation of hepatic transaminases occurred after LC in all groups. Group A had a higher adherence score than groups B and C and was associated with the least predictable technique. Conclusion: LC can be performed using different techniques, although the use of EBVS is highly recommended.
Keywords: Biliary Tract Surgical Procedures; Cholecystectomy, Laparoscopic; Cystic Duct; Gallbladder Diseases